Comparative study on efficacy of SNOT 22 outcome in nasal surgery using teflon splinting for chronic rhinosinusitis - K. B., Sajitha; B., Vibha; Thomas, Norma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: CRS is defined as inflammation in the nose and paranasal sinus and it is characterized by two or more cardinal symptoms. There is a growing need for a simple, reliable, system-specific standardized outcome measure that can help us explore CRS in a more uniform way and help us to take into account patients’ HRQoL. SNOT covers a broad range of health and health-related quality of life problems including physical problems, functional limitations, and emotional consequences. Methods: we report a case series of 60 patients, divided into 2 groups of 30 each. 1st group underwent FESS+septoturbinoplasty while the 2nd group underwent FESS+septoturbinoplasty with teflon splinting. Patients were asked to score their symptoms on SNOT 22 questionnaire pre-operatively and post-operatively. Results: Significant changes were noted in nasal related and quality of life domain and less significant changes noted in ear/facial related and psychological domains in group 2. Conclusions: patient-based outcome measures like SNOT 22, is helpful tool for quantifying changes in symptoms and useful for predicting post-operative improvement. It is both patient and researcher-friendly.